Biosynthesis of polyketides by two type III polyketide synthases from Aloe barbadensis. Issue 5 (3rd May 2020) - Liu, Ai-Jing; Xie, Ke-Bo; Liu, Yu-Yu; Sui, Song-Yang; Chen, Ri-Dao; Chen, Da-Wei; Liu, Ji-Mei; Yang, Lin; Dai, Jun-Gui
Abstract: Various bioactive polyketides have been found in Aloe barbadensis. However, the polyketide synthases (PKSs), which participate in biosynthesis of polyketides in A. barbadensis remain unknown. In this study, two type III PKSs (AbPKS1 and AbPKS2) were identified from A. barbadensis . AbPKS1 and AbPKS2 were able to utilize malonyl-CoA to yield heptaketides (TW93a and aloesone) and octaketides (SEK4 and SEK4b), respectively. AbPKS1 also exhibited catalytic promiscuity in recognizing CoA thioesters of aromatics to produce unusual polyketides. What Is more, a whole cell biocatalysis system with the capability of producing 26.4 mg/L of SEK4/SEK4b and 2.1 mg/L of aloesone was successfully established. Graphical Abstract: